Cryptanalysis of the CLR-cryptosystem - Micheli, G; Weger, VW (Springer US, 2018)
t In this paper we break a variant of the El-Gamal cryptosystem for a ring action of the matrix space E(m) p on Z/pZ × Z/p2Z ×···× Z/pmZ. Also, we describe a general vulnerability of the protocol using tools from p-adic analysis.